If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 2(X + 11) Reorder the terms: 4 + 5x = 2(X + 11) Reorder the terms: 4 + 5x = 2(11 + X) 4 + 5x = (11 * 2 + X * 2) 4 + 5x = (22 + 2X) Solving 4 + 5x = 22 + 2X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 22 + -4 + 2X Combine like terms: 4 + -4 = 0 0 + 5x = 22 + -4 + 2X 5x = 22 + -4 + 2X Combine like terms: 22 + -4 = 18 5x = 18 + 2X Divide each side by '5'. x = 3.6 + 0.4X Simplifying x = 3.6 + 0.4X
| 6+3i= | | -4(j+14)=-12 | | 17-9(.8)=3+12.8 | | x+x(0.13)=200 | | y=0.15x+40 | | -1+10x=-81 | | 6x^2=5-13x | | (11)7X(11)6= | | 3(m-14)=6 | | 4/20x=10/20 | | -18÷2/3 | | 2x+8=4x+3-2x+5 | | 15w-14w-1=6 | | 1-x=-4 | | 3(y-10)+1=-33(y-8) | | 7x+36=x | | 1+x+1-9=x-7 | | 32.7=2*pi*r | | 3r+20r-(-12)=-11 | | 2/6(4x-1) | | x+x(0.13)=1200 | | 1+x+-9=x-7 | | 5x+4(2)=-7(x-3) | | 2x/5-x-2/10=2 | | 24=-6(x-5) | | e^6x=64 | | 9/12-3/12 | | 3x^(2/3) | | 8=-4(v-20) | | 2x+log(9-x)=2 | | 7(x+7)+3=7x+6 | | 8x^2-2y=8 |